Model Komunikasi Antar Guru Dan Siswa Penyandang Disabilitas Dalam Memotivasi Belajar(Studi Kasus Di SMPLB Negeri Dompu) - Syatriadin Syatriadin (Journal on Education, 2024)
Interpersonal communication is a process of sending and receiving messages between two people or between a small group of people, with some effect and some resulting feedback. The focus of this research is on the pattern of communication between teachers and students with disabilities in motivating student learning. This study uses a qualitative approach, which is descriptive as an approach that tends to use data analysis. Data obtained through observation, interviews and documentation. Techniques The determination of informants was carried out using a side purposive technique, on 9 selected informants. Based on the results of the study that the communication pattern between teachers and students with disabilities in motivating learning is to use the wheel communication pattern. The teacher's role in motivating learning includes: (1) conversations/questions and answers (2) fostering self confidence (3) reading and writing activities (4) providing opportunities to come forward.